2018
DOI: 10.1177/0042085918801436
|View full text |Cite
|
Sign up to set email alerts
|

Pay-for-Performance Reform Programs: It’s More Than the Money!

Abstract: This study evaluated five teachers from a middle school with a history of low-performances and high teacher turnover. This school participated in a reform program, Pay-For-Performance, where they received financial bonuses to increase performances on literacy and mathematics assessments. Additional requirements included participation in workshops, and planning and data discussions. Despite appreciation for incentives, teachers credited these professional development opportunities and district's growth model as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Research has suggested that school leadership can foster resilience, agency, and possibility by offering trust and support to novices through teacher support groups and responsive, non-judgmental coaching (Fisher-Ari et al, 2017). By creating induction processes and practices that focused on teachers’ self-identified learning needs and supporting them with professionalizing systems of accountability for growth according to those goals, school leaders can create a climate where new teachers learn from others and share their own knowledge and expertise (Howard & Miller, 2022; Engvik & Emstad, 2017). This requires school leaders to broker reciprocal and supportive relationships between new teachers and others within the school such as coaches, grade-level peers, and other mentors (Ingersoll & Strong, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has suggested that school leadership can foster resilience, agency, and possibility by offering trust and support to novices through teacher support groups and responsive, non-judgmental coaching (Fisher-Ari et al, 2017). By creating induction processes and practices that focused on teachers’ self-identified learning needs and supporting them with professionalizing systems of accountability for growth according to those goals, school leaders can create a climate where new teachers learn from others and share their own knowledge and expertise (Howard & Miller, 2022; Engvik & Emstad, 2017). This requires school leaders to broker reciprocal and supportive relationships between new teachers and others within the school such as coaches, grade-level peers, and other mentors (Ingersoll & Strong, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Decisions about mandated, external assessments and scripted reform models, and opportunities and resources for professional development have significant influence on teachers’ development and commitment (Datnow & Castellano, 2000). Teacher autonomy and local decisions about instructional resources and pedagogies can disrupt the standardization narrative while opening spaces for responsive, differentiated curriculum and assessment (Howard & Miller, 2022). A flattened hierarchy honors educators’ expertise and knowledge creation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation